The Role of Digital Technology in Overcoming Game Addiction in Post-COVID-19 - Fitria, Ika; Pangestu, Budi; Mardikawati, Budi; Tjahyadi, Indra; Bawamenewi, Arozatulo (Al-Hijr: Journal of Adulearn World, 2024)
This article aims to describe the role of digital technology in overcoming game addiction in post-covid-19. One of the problems that has received widespread attention from society is online game addiction. Teenagers are one of the largest age groups who experience game addiction. The aspects that impact online game addiction are life aspects, health aspects, psychological aspects, academic aspects, financial aspects, and social aspects. The purpose of the study is to examine alternatives to prevent online game addiction in adolescents in the midst of the Covid-19 pandemic by using digital technology in the form of digital literacy. This problem utilizes a qualitative approach using the questionnaire method. In this process, the role of digital technology has become an alternative to prevent addiction to playing games. Many of the researchers focus more on educating about game addiction, but forget the facts about efforts to prevent online games. The results of this study explain that the role of digital technology can overcome game addiction. The conclusion of the research results on the role of digital technology in overcoming game addiction in post covid-19 is that it can help efforts in overcoming game addiction by using digital technology parameters. The limitation of this research is that researchers only conduct research in post covid-19, and the time used is also limited to conduct research, researchers hope that future researchers can take greater action than the current research using better methods or technology and a larger scope.